2020
DOI: 10.3390/ijerph17041142
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation with a Bioactive Melon Concentrate in Humans and Animals: Prevention of Oxidative Damages and Fatigue in the Context of a Moderate or Eccentric Physical Activity

Abstract: Exercise is recognized to provide both physical and psychological health benefits. However, oxidative stress can occur and induce muscular damages. SOD B ® M is a melon concentrate, well known to counteract oxidative stress and prevent its side effects. The present study aimed to evaluate the potential of the melon concentrate in the context of both a strong and isolated effort associated with deleterious effects, and a moderate and regular physical activity considered as beneficial. First, a preclinical study… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…The study demonstrated a lower initial inflammatory state in the SODB group which was maintained during and after the training session, whereas the placebo group experienced a significant increase in inflammation. The authors identified an increase in the PARγ coactivator 1-alpha (PGC-1alpha) and the consequent myosin fibers rearrangement the lading pathway for adaptation to effort, endurance, performance [ 179 ].…”
Section: Sod As a Pharmacological Agentmentioning
confidence: 99%
“…The study demonstrated a lower initial inflammatory state in the SODB group which was maintained during and after the training session, whereas the placebo group experienced a significant increase in inflammation. The authors identified an increase in the PARγ coactivator 1-alpha (PGC-1alpha) and the consequent myosin fibers rearrangement the lading pathway for adaptation to effort, endurance, performance [ 179 ].…”
Section: Sod As a Pharmacological Agentmentioning
confidence: 99%
“…During the last decade, efforts to valorize food by-products have increased demands for testing different extraction techniques to isolate beneficial enzymes, for instance, from melon pulp and juice. In this context, it was demonstrated that the oral daily intake of melon juice rich in SOD helps to reduce symptoms of body stress and fatigue [ 18 , 19 ]. In the human body, defenses against free radicals are due to the synergic actions of the inner SOD and CAT antioxidant enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…In the human body, defenses against free radicals are due to the synergic actions of the inner SOD and CAT antioxidant enzymes. Since their finding, many studies have been published, and recently, the efficacy of melon’s SOD supply in controlled clinical studies has proven how the SOD provides preventive and restorative effects from oxidative stress and gives inflammation relief in almost all tissues [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Напиток предупреждает окислительный стресс икроножных мышц вследствие их перегрузки, что позволяет людям, занимающимся спортом и прочей физической активностью, быстрее восстанавливаться после полученных нагрузок, меньше уставать. [16]…”
Section: помогает справляться с нагрузкамиunclassified